Design, synthesis, and antiprotozoal evaluation of new 2, 9‐bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthroline derivatives. (17th January 2018) - Guillon, Jean; Cohen, Anita; Das, Rabindra Nath; Boudot, Clotilde; Gueddouda, Nassima Meriem; Moreau, Stéphane; Ronga, Luisa; Savrimoutou, Solène; Basmaciyan, Louise; Tisnerat, Camille; Mestanier, Sacha; Rubio, Sandra; et al.
Abstract : A series of new 2, 9‐bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthroline derivatives was synthesized, and the compounds were screened in vitro against three protozoan parasites ( Plasmodium falciparum, Leishmania donovani, and Trypanosoma brucei brucei ). Biological results showed antiparasitic activity with IC50 values in the μm range. The in vitro cytotoxicity of these molecules was assessed by incubation with human HepG2 cells; for some derivatives, cytotoxicity was observed at significantly higher concentrations than antiparasitic activity. The 2, 9‐bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthroline1h was identified as the most potent antimalarial candidate with ratios of cytotoxic‐to‐antiparasitic activities of 107 and 39 against a chloroquine‐sensitive and a chloroquine‐resistant strain of P. falciparum, respectively. As the telomeres of the parasite P. falciparum are the likely target of this compound, we investigated stabilization of the Plasmodium telomeric G‐quadruplexes by our phenanthroline derivatives through a FRET melting assay. The ligands1f and1m were noticed to be more specific for FPf8T with higher stabilization for FPf8T than for the human F21T sequence. Abstract : A new series of 2, 9‐bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthrolines was synthesized and screened in vitro against three protozoan parasites ( Plasmodium falciparum, Leishmania donovani, and Trypanosoma brucei brucei ). Biological results showed good antiparasitic activity with IC50 values in the μm range.